INTERAKSI OWNERSHIP RETENTION DAN JUMLAH DIREKSI TERHADAP NILAI UNDERPRICING - Taolin, Maximus Leonardo; Mauk, Sarlince Sandy (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This study aims to analyze the interaction of the number of management (board of directors and commissioners) and old ownership (ownership retention) on underpricing at the initial Public offeringse. The company's success in obtaining revenue from the IPO is marked by an increase in the number of shares that are maintained in large numbers as well as the number of commissioners and company designs which have an impact on the initial share price experiencing underpricing. The results of this study support this opinion. So it can be said that the interactions that occur at the beginning of the stock offering period can be used for investors in determining the direction of their investment decisions. The regression results shown from the SPSS 22 software show that the interaction between the number of company management and the old ownership held by the issuer has an effect on underpricing. Thus, the ownership retained by the issuer is a moderating variable that can weaken or strengthen the influence of the Board and commissioners on underpricing.